Finite-Element Simulation on NPGCS Precast Shear Wall Spatial Structure Model - Dongyue Wu; Shuting Liang; Mengying Shen; Zhengxing Guo; Xiaojun Zhu; Chongfang Sun; Qian Fu (Advances in Civil Engineering)
Seismic performance is basically required in precast shear wall. This study focuses on evaluation and improvement on precast shear wall seismic performance. By carrying out the finite-element simulation on a precast shear wall spatial model with new connector from a practical high-rise precast residential building, which was named as NPGCS and experimentally tested by low-cyclic reversed lateral loads in early studies, the performance results including strengths, stiffness, stress, and concrete damage ratio distributions were obtained, and the reliability of NPGCS spatial model was verified. According to the testing results, the finite-element simulation for the NPGCS spatial model is reliable and relatively accurate, especially for applying contact and beam elements into numerical analysis of precast interfaces and dowel shear actions, respectively. The strengths, stiffness, stress, and concrete damage ratio distributions from the simulation also supported the experimental results and conclusions.